Pengetahuan Dan Peran Keluarga Dalam Perilaku Merokok Di Nglampengan Bantul Tahun 2018 - Woro Ispandiyah ((JKG) Jurnal Keperawatan Global, 2019)
Background: Based on the information Head of Hamlet Nglampengan smoking is still the main topic that can cause very harmful effects, especially the more dominant inhaling cigarette smoke, the activity has become a hobby among people, especially men in Nglampengan Village Temuwuh Village Dlingo District, Bantul Regency. Awareness, customs and culture are some of the factors that make smoking a common thing, although smokers know the danger and its impact, but still do. The general purpose of this research is to know the influence of knowledge and family role to smoking behavior in Nglampengan Village Temuwuh Village Dlingo District, Bantul Regency. Method: The research type is descriptive quantitative research with cross-sectional research design. The population in this study as many as 53 heads of households where researchers took from the population of head of household Nglampengan Village Temuwuh Village District DlingoBantul Regency is still actively smoking in the house. Sampling using samples saturated as many as 53 household heads. Result: The result of Chi Square test shows that there is no effect of between knowledge with smoking behavior with result of significant value (Pvalue) influence between knowledge with smoking behavior is 1.000 (Pvalue>a). The influence of family role with smoking behavior with the result of significant value (Pvalue) equal to 0.037 (Pvalue <a). Conclusion: There is not significant influencebetween knowledge and smoking behavior, the influenceof family role with smoking behavior.